Pengaruh Penambahan Tepung Kacang Merah pada Grit Jagung dan Suhu Barrel Terhadap Sifat Fisik Ekstrudat - Dian Kharisma Rahmawati; Joko Nugroho Wahyu Karyadi; Devi Yuni Susanti; Ailsa Saraswati Samodra; Riski Sri Mahanani; Vincentius Ferry Surya Dwinata; Prasetya Febriyansyech Personanta Sinuhaji (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2024)
Corn is widely processed into the main ingredient in making snacks but has a low protein content. Therefore, it is necessary to add protein in the form of beans, especially red beans. The physical characteristics of extrudate as a result of extrusion processing can be determined by material composition and barrel temperature factors. This study aims to determine the effect of material composition treatment and barrel temperature on the physical properties of extrudate made from corn grit and red bean flour. There are three levels of red bean addition, namely, 10%, 20%, and 30% with variations of temperature 120°C, 130°C, and 140°C. Physical quality parameters measured in the form of moisture content, expansion ratio, bulk density, particle density, water absorption index (WAI), water solubility index (WSI), and hardness. The extrudate produced is in accordance with SNI with a moisture content of < 4%. An increase in barrel temperature affects the increase in expansion ratio and decrease in moisture content, bulk density, particle density, WAI, WSI, and hardness. The addition of red bean flour caused an increase in moisture content, bulk density, particle density, hardness, and WSI and decrease in the expansion ratio and WAI.